Synergism of Consortium of Heterotrophic Bacterial Strains with Pistia stratiotes L. and Salvinia molesta D. Mitch as Biophytoremediator for Heavy Metal Removal in Domestic Wastewater - Lud Waluyo; Nyono; Sukarsono; Atok Miftachul Hudha; Abdulkadir Raharjanto (HAYATI Journal of Biosciences, 2024)
High levels of organic matter and heavy metals in domestic wastewater can increase the pollution of water bodies. The water pollution results correspond to the degree of public health. Waste must be controlled and processed first using management methods such as biophytoremedyator to decrease the rate of pollution because its advantages do not negatively impact public health and the environment. Biophytoremediation offers a better alternative method to repair environmental conditions by combining microorganisms and plants. This study aimed to analyze the effect of heterotrophic bacterial strains with Pistia stratiotes L. and Salvinia molesta D. Mitch for heavy metal removal in domestic wastewater. It also investigated the influence of heterotrophic bacterial strains with Pistia stratiotes L. and Salvinia molesta D. Mitch which were also carried out to observe the BOD and COD levels. The results showed decreased heavy metal levels from the three treatment groups. The consortium treatment group of heterotrophs and Salvinia molesta D. Mitch bacteria strains reduced heavy metal levels faster than the other groups by 59%. In addition, it is also able to reduce BOD and COD levels. This study has shown the significant effect of combining heterotrophic bacterial (HB) strains with Pistia stratiotes L. or Salvinia molesta D. Mitch for heavy metal removal in domestic wastewater.